High-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film and preparation method thereof

By using pre-plasticized polyvinyl alcohol and thermoplastic starch composite materials, combined with modified cellulose and crosslinking agents, the problem of difficult degradation and high processing costs of food plastic wrap materials is solved, and a high-performance, low-cost and degradable food packaging film is achieved.

CN119570182APending Publication Date: 2025-03-07HE NAN NAI KE DA CAI SE YIN SHUA YOU XIAN GONG SI

Patent Information

Application Number
CN202411667361.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing food plastic wrap materials are difficult to degrade in the natural environment, resulting in "white pollution" problems, and at the same time, high processing costs, hindering the development of industrialization.

Method used

Using high-performance degradable polyvinyl alcohol-thermoplastic starch composite materials, modified cellulose and crosslinking agent are introduced to form a composite film with good mechanical properties and barrier properties through the modification of pre-plasticized polyvinyl alcohol and thermoplastic starch.

Benefits of technology

It realizes the low cost, high performance and degradability of food packaging film, reduces the risk of "white pollution", and reduces production costs, and has industrialization prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570182A_ABST
    Figure CN119570182A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film which is prepared from the following raw materials in parts by weight: 50-65 parts of pre-plasticized polyvinyl alcohol, 35-50 parts of thermoplastic starch, 1-10 parts of modified cellulose, 0.1-3 parts of a cross-linking agent, 0.1-0.5 part of a bacteriostatic agent, 0.1-1 part of an antioxidant and 1-3 parts of a lubricant, and also discloses a preparation method of the product. The polyvinyl alcohol-starch-based composite film prepared by the method disclosed by the invention can be completely biodegraded in a natural environment, serious white pollution caused by discarding plastics into the natural environment is avoided, the polyvinyl alcohol-starch-based composite film is safe and environment-friendly, and meanwhile, cellulose components can be derived from grain processing by-products, so that high-added-value utilization of agricultural and sideline products is also facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic films, and in particular relates to a high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film and a preparation method thereof. Background Art

[0002] At present, the common food cling film on the market is petroleum-based packaging materials (such as plastics), which have the advantages of good mechanical properties, simple processing, low cost, and excellent water vapor barrier performance. However, most food preservation packaging has high recycling costs and is difficult to degrade in the natural environment. A large amount of food packaging materials discarded in the natural environment will cause serious "white pollution", and the plastic microparticles produced by decomposition will also have adverse and far-reaching effects on the environment and human body. In addition, the energy crisis also urgently needs to find sustainable alternatives.

[0003] Starch is degradable, renewable, safe and non-toxic, widely available and low-cost, and has received widespread attention as a substitute for petroleum products. However, the starch molecular structure contains a large number of hydrogen bonds formed by hydroxyl groups, which is difficult to melt process and has poor water resistance. It needs to be plasticized and modified. Among them, the blending modification does not change the molecular structure of starch, the operation is simple, and it can significantly improve the mechanical and barrier properties of starch. In the degradable resin that can be compounded with starch, the processing temperature of polyvinyl alcohol (PVA) is compatible with starch, the processability is good, it is non-toxic, and it has good compatibility with starch. The introduction of polyvinyl alcohol can improve the flexibility of thermoplastic starch (TPS), improve its water vapor and gas barrier properties, and retain transparency. In the extrusion process, cross-linking agents such as citric acid are introduced to moderately cross-link the starch to form a three-dimensional network, change the starch aggregation structure, and further improve the mechanical properties and barrier properties. In addition, the large number of hydroxyl groups contained in the cellulose molecular structure can form hydrogen bonds with molecules such as starch as fillers and produce a network structure, which can effectively improve the structural uniformity and density of the film. In addition, this hydrogen bonding effect also helps to reduce the diffusion coefficient of water molecules and gases in the composite film, improving the water and gas barrier properties of the film. At the same time, the introduction of non-toxic natural antibacterial substances into the system can give the polyvinyl alcohol-thermoplastic starch composite film antibacterial properties and improve the food preservation ability.

[0004] Wang Sheng et al. (Wang Sheng. Preparation and performance study of polyvinyl alcohol / soluble starch cling film [D]. Zhejiang A&F University, 2023.) used the casting method to prepare polyvinyl alcohol / soluble starch composite film, which has the advantages of good transparency, good water resistance and antibacterial properties. However, the casting method requires a large amount of solvent and the drying step takes too long, which is complex to process, has high energy consumption and high production costs, and is difficult to industrialize. Xu Lifan et al. (Xu Lifan. Study on extrusion blow molding process and properties of polyvinyl alcohol / starch film [D]. Beijing University of Chemical Technology. 2008) used extrusion granulation and blow molding process to continuously prepare polyvinyl alcohol / starch film. The water resistance of the film was improved by treating starch with a coupling agent. Although the preparation process has industrial prospects, the mechanical properties and water vapor resistance of the material still do not meet the use requirements.

[0005] The Chinese invention patent with patent number 202410304038.1 discloses a modified polyvinyl alcohol food preservative film and a preparation method thereof. Polyvinyl alcohol and cellulose nanofibers are cross-linked using gallic acid, and a polyvinyl alcohol-cellulose nanofiber composite film is prepared by a casting method. Although the film is safe, environmentally friendly and antibacterial, the casting method is complex, energy-intensive and requires large equipment investment, which hinders industrialization; the Chinese invention patent with patent number 202410654809.X discloses a method for preparing walnut shell lignin-enhanced polyvinyl alcohol food preservative film. The lignin-polypeptide network constructed by this invention significantly improves the mechanical properties of the polyvinyl alcohol film. The prepared UV-resistant and antioxidant food preservative film is pollution-free, degradable, and has good UV barrier and antioxidant properties. However, the preparation process requires a large amount of ethylene glycol solvent, a large amount of energy consumption, and low production efficiency.

[0006] At present, most of the preparation methods of degradable food cling film are solution casting, but its industrial development is hindered by its high cost. Compared with the solution casting method, the production method of melt extrusion blow molding / calendering has low manufacturing cost, high production efficiency, and strong selectivity of film performance. However, in actual production, the polyvinyl alcohol / starch composite system is very easy to thermally decompose, discolor, and become brittle during thermoplastic processing, and loses processing performance and use performance, which is also the difficulty restricting the industrialization of polyvinyl alcohol / starch-based food cling film. Summary of the invention

[0007] The purpose of the present invention is to provide a high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film, and at the same time provide a preparation method of the preservative film, so as to realize the industrialization of biodegradable food packaging film and reduce the "white pollution" of food packaging film.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] A high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 50-65 parts of pre-plasticized polyvinyl alcohol, 35-50 parts of thermoplastic starch, 1-10 parts of modified cellulose, 0.1-3 parts of a cross-linking agent, 0.1-0.5 parts of an antibacterial agent, 0.1-1 parts of an antioxidant, and 1-3 parts of a lubricant.

[0010] Preferably, a high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is made of the following raw materials in parts by weight: 60-65 parts of pre-plasticized polyvinyl alcohol, 40-50 parts of thermoplastic starch, 1-5 parts of modified cellulose, 0.1-3 parts of a cross-linking agent, 0.1-0.5 parts of an antibacterial agent, 0.1-1 parts of an antioxidant, and 1-3 parts of a lubricant.

[0011] Preferably, the pre-plasticized polyvinyl alcohol is prepared by the following method: adding polyvinyl alcohol to a blender, dividing the compound plasticizer into three equal parts, and adding the compound plasticizer into the stirred polyvinyl alcohol in three batches, with an interval of 10-20 minutes between each batch, and stirring for 10-20 minutes after adding the last batch of compound plasticizer, to finally form pre-plasticized polyvinyl alcohol pellets with fluffy particles, good toughness, and clean appearance; the compound plasticizer is composed of water and glycerol, and the volume ratio of water to glycerol is 1:5; the ratio of the number of polyvinyl alcohol to the compound plasticizer is (4-6):3; the stirring temperature is 80-120°C, and the stirring rate is 80-120rpm.

[0012] Preferably, the volume ratio of water to glycerol is 1:5; the volume ratio of polyvinyl alcohol to compound plasticizer is 5:3.

[0013] Polyvinyl alcohol has a regular molecular structure, high crystallinity, and a melting temperature of up to 190°C. However, polyvinyl alcohol begins to decompose at 140°C, and the decomposition temperature is much lower than the processing temperature, making polyvinyl alcohol difficult to process. Similarly, starch molecules contain a large number of hydrogen bonds, and the molecular chain interaction force is large. The starch melting temperature is much higher than the decomposition temperature, and the film is hard and brittle. Therefore, both polyvinyl alcohol and starch need to be pre-plasticized. Considering that when polyvinyl alcohol and starch are mixed and plasticized together, there is a competitive relationship between the two. The ability of starch to absorb plasticizers is much higher than that of polyvinyl alcohol resin, which makes the plasticization of polyvinyl alcohol resin incomplete. Defects such as film breakage and poor appearance are prone to occur during processing. Therefore, polyvinyl alcohol and starch need to be plasticized separately.

[0014] Even if polyvinyl alcohol is plasticized alone, there are often cases of incomplete plasticization and partial inability to absorb plasticizers, so the plasticization process needs to be properly controlled. Above the glass transition temperature of polyvinyl alcohol (>85°C), the polyvinyl alcohol resin is in a partially high-elastic state, and the chain segment movement intensifies. When a plasticizer is introduced at this time, the plasticizer molecules can easily enter the molecular chains of polyvinyl alcohol and play a plasticizing role. At the same time, adding plasticizers in batches allows polyvinyl alcohol to "gradually" absorb plasticizers, avoiding the defect of excessive plasticization of the outer layer of polyvinyl alcohol pellets while the core layer remains hard due to one-time addition. Therefore, the key to pre-plasticization of polyvinyl alcohol is to reasonably control the plasticization temperature, plasticizer dosage, number of additions, plasticization time, etc.

[0015] Preferably, the thermoplastic starch is prepared by the following method: 90-110 parts of corn starch are mixed with 15-25 parts of glycerol, 15-25 parts of acetyl tributyl citrate, 1-3 parts of stearic acid, 7-9 parts of acetyl tributyl citrate and 0.5-1.5 parts of coupling agent, and the mixture is stirred in a high-speed mixer for 8-12 minutes, and sealed and allowed to stand for 10-14 hours; the mixture is then conveyed to a twin-screw extruder for granulation to obtain thermoplastic starch granules; the temperature of each heating section of the extruder is 140-155° C., the screw speed is 40-60rpm, and the feeding speed is set to 3-5rpm.

[0016] To achieve better results, preferably, the thermoplastic starch is prepared by the following method: 100 parts of corn starch are mixed with 20 parts of glycerol, 20 parts of acetyl tributyl citrate, 2 parts of stearic acid, 8 parts of acetyl tributyl citrate and 1 part of a coupling agent, and the mixture is placed in a high-speed mixer and stirred for 10 minutes, and then sealed and allowed to stand for 12 hours; the mixture is then conveyed to a twin-screw extruder for granulation to obtain thermoplastic starch granules; the temperature of each heating section of the extruder is 140-155°C, the screw speed is 40-60rpm, and the feeding speed is set to 4rpm.

[0017] Sorbitol has good compatibility with starch. When combined with starch, it can improve the toughness of starch-based films and the apparent quality of the product. When used in combination with glycerol, it can further improve the elongation at break of starch-based films, improve film-forming properties and film toughness, and extend the storage period. On this basis, the introduction of a coupling agent can improve the compatibility of starch and PVA phases, improve the transparency and strength of the composite film, and also optimize the water resistance of the starch-based film.

[0018] Preferably, the modified cellulose is stearic acid-modified cellulose; the stearic acid-modified cellulose is prepared by the following method: 1-3 parts of cellulose are mixed with 15-25 parts of anhydrous ethanol, ultrasonically treated for 25-35 minutes, then 1-3 parts of stearic acid are added, and ultrasonic treatment is continued for 25-35 minutes, and then heated and stirred at 75-85°C for 3-5 hours, filtered, and dried.

[0019] To achieve better results, the modified cellulose is cellulose modified with stearic acid; the stearic acid modified cellulose is prepared by the following method: 2 parts of cellulose are mixed with 20 parts of anhydrous ethanol, ultrasonically treated for 30 minutes, then 2 parts of stearic acid are added, and ultrasonic treatment is continued for 30 minutes, and then heated and stirred at 80°C for 4 hours, filtered and dried.

[0020] Cellulose (CSC) can be derived from natural materials such as food processing byproducts. It is renewable and degradable. It has a linear polysaccharide structure and can be connected with starch, PVA resin, etc. through hydrogen bonds. When introduced into the polyvinyl alcohol-thermoplastic starch composite system, it can not only enhance the strength of the composite film, but also reduce the porosity of the film, increase the diffusion path of gas and water, and thus improve the film's water vapor barrier performance. However, due to its own structure, cellulose is easy to agglomerate and is difficult to disperse evenly in the resin matrix during processing. Therefore, it is necessary to modify its surface to improve its dispersibility in the resin.

[0021] Preferably, the crosslinking agent is citric acid; the carboxyl group in the citric acid molecule can react with the hydroxyl group of the polysaccharide to form a covalent diester bond between the molecules, thereby playing a crosslinking role. As a crosslinking agent for starch-based materials, citric acid has the advantages of safety, environmental protection, good crosslinking effect, and a wide range of applications. By introducing a crosslinking structure into the polyvinyl alcohol-thermoplastic starch composite system, the mechanical strength and water resistance of the material can be improved, but the degree of crosslinking needs to be appropriate. Excessive crosslinking will cause the starch system to lose its thermoplastic properties and make processing difficult. Citric acid can react with the hydroxyl group of the polysaccharide to form a covalent diester bond between the molecules, thereby playing the role of a crosslinking agent.

[0022] Preferably, the antibacterial agent is one of citric acid, tartaric acid, plant essential oil, tea polyphenols, apple pomace polyphenols, grapefruit seed extract, benzoic acid, and lauroyl arginine ethyl ester hydrochloride.

[0023] Preferably, the antioxidant is at least one of phenolic antioxidants, vitamin E, thioesters, and phosphite antioxidants.

[0024] Preferably, the lubricant is one of stearic acid, acrylate, polyethylene wax powder and silicone.

[0025] Preferably, the coupling agent is one of a silane coupling agent, a titanate coupling agent and an aluminate coupling agent.

[0026] The preparation method of the high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film comprises the following steps:

[0027] S1. Raw material mixing: The raw materials are transported from the storage bin to the mixing hopper through the feeding system according to the proportion, the materials are dry mixed in the mixing hopper, and then filtered and processed by the metal separator to filter out the large impurities and entrained metal debris in the materials, and then transported to the extruder section; the premixing speed is 300-500rpm, the premixing time is 3-5min, and the temperature is room temperature; the room temperature is 25°C;

[0028] S2, extrusion plasticization: the material enters the extruder section, and under the heating and screw shearing action of the single screw extruder, the material is melted, mixed and appropriately cross-linked, and extruded through the die under the conveying action of the screw to obtain a polymer annular sheet; the extrusion section temperature is 160-180°C, the die temperature is 205-220°C, the single screw speed is set to 60-100rpm, and the extruder extruded sheet thickness is 500-800μm;

[0029] S3, film blowing: the sheet is blown by compressed air at the die of the extruder to form a film and stretched to obtain a semi-finished fresh-keeping film; the compressed air pressure for film blowing is 0.6-0.8MPa; the film stretching rate is set to 200-450mm / min; in this process, attention should be paid to the proper coordination of the extrusion rate and the film blowing stretching rate to ensure that the packaging film product is fully formed and has uniform thickness;

[0030] S4. Slitting and packaging: The packaging film that has passed the thickness and appearance inspection is first trimmed on both sides by a trimmer, then rolled into bundles on a winder, and then cut into the specifications required by the user by a slitting machine for packaging to obtain the final food packaging film product. The thickness of the food preservative film is 25-35μm.

[0031] The principle of the invention is: rationally constructing a composite system, selecting widely available, renewable and degradable starch as a matrix, selecting polyvinyl alcohol and thermoplastic starch with good compatibility with starch and similar processing temperature range for composite modification to improve its mechanical properties and transparency; in order to improve its processability and water resistance, plasticizing modification is performed on them respectively; at the same time, the structure of the composite system is designed and regulated, a coupling agent is selected to modify the starch, and a partial cross-linking structure is introduced into the system to improve the interface condition of the two phases, increase the compatibility of the two phases, and thus improve the mechanical strength and water resistance of the film; in addition, cellulose with organic surface modification is introduced into the system, and a layered or mesh filler structure can be introduced into the system to increase the path of water vapor diffusion, thereby improving the performance of blocking water vapor; an antibacterial agent is introduced into the system to give the composite film the function of antibacterial preservation, and through optimized design and regulation, the successful preparation of a polyvinyl alcohol-thermoplastic starch-based composite food film with low cost, high performance, thermoplastic processability and degradability is finally achieved.

[0032] The present invention has the following advantages and beneficial results:

[0033] The polyvinyl alcohol-starch-based composite film prepared by the present invention can be thermoplastically processed by ordinary plastic molding machinery, with high processing efficiency, low cost, and easy control of film parameters. Therefore, the overall preparation process has low energy consumption and low production cost, and the overall manufacturing cost is less than 15,000 yuan / ton.

[0034] The polyvinyl alcohol-starch-based composite film prepared by the present invention can be completely biodegraded in the natural environment, avoiding the serious "white pollution" caused by discarding plastics into the natural environment. It is safe and environmentally friendly. At the same time, the cellulose component can be derived from food processing by-products, which also contributes to the high added value utilization of agricultural and sideline products.

[0035] The polyvinyl alcohol-starch-based composite film prepared by the present invention has excellent mechanical properties and water vapor barrier properties by rationally designing the composite system and regulating the structure. The film has a tensile strength of ≥20MPa, a tear strength of ≥40KN / m, an elongation at break of ≥200%, and good water vapor barrier properties (water vapor permeability coefficient ≤1.0×10 -12 g / (cm·s·Pa), oxygen transmission rate ≤2.0×10 -5 g / (m 2 ·d·Pa)).

[0036] The polyvinyl alcohol-starch-based composite film prepared by the present invention can prepare a film with certain transparency by adjusting the ratio of the polyvinyl alcohol resin to the starch, regulating the two-phase distribution and the interface state, and is conducive to the application as a food packaging film. The present invention adopts a step-by-step processing method, plasticizes the polyvinyl alcohol and starch in advance, and regulates the microstructure of the polyvinyl alcohol / starch composite system by a reasonable design processing method, and finally prepares a polyvinyl alcohol / thermoplastic starch food preservative film with a low price, thermoplastic processing, good use performance (mechanical properties, water vapor isolation performance, etc.), and completely biodegradable, and the product has a prospect of industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The present invention is a flow chart for preparing the high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with examples and appendices under different conditions, but the specific implementation methods of the present invention are not limited thereto.

[0039] Example 1

[0040] The preparation method of pre-plasticized polyvinyl alcohol is as follows: 60 parts of a compound plasticizer are divided into three parts, and the parts are added into 100 parts of polyvinyl alcohol being stirred in three batches, with an interval of 15 minutes between each batch, and the last batch of compound plasticizer is added and then stirred for 15 minutes, so as to finally form pre-plasticized polyvinyl alcohol granules with fluffy particles, good toughness and clean appearance; the compound plasticizer is composed of water and glycerin, and the volume ratio of water to glycerin is 1:5; the stirring temperature is 90°C, and the stirring speed is 90rpm.

[0041] The preparation method of thermoplastic starch is as follows: 100 parts of corn starch are mixed with 20 parts of glycerol, 20 parts of acetyl tributyl citrate, 2 parts of stearic acid, 8 parts of acetyl tributyl citrate and 1 part of coupling agent, and stirred in a high-speed mixer for 10 minutes, and sealed and left to stand for 12 hours; then the mixture is transported to a twin-screw extruder for granulation to obtain thermoplastic starch granules; the temperature of each heating section of the extruder is 150-155°C, the screw speed is 55-60rpm, and the feeding speed is set to 4rpm. The coupling agent is a titanate coupling agent.

[0042] The modified cellulose is cellulose modified with stearic acid; the preparation method of the cellulose modified with stearic acid is as follows: 2 parts of cellulose are mixed with 20 parts of anhydrous ethanol, ultrasonically treated for 30 minutes, then 2 parts of stearic acid are added, and ultrasonic treatment is continued for 30 minutes, and then heated and stirred at 80°C for 4 hours, filtered, and dried.

[0043] Example 2

[0044] The preparation method of pre-plasticized polyvinyl alcohol is as follows: 60 parts of a compound plasticizer are divided into three parts, and the parts are added into 80 parts of polyvinyl alcohol being stirred in three batches, with an interval of 20 minutes between each batch, and the last batch of compound plasticizer is added and stirred for 20 minutes, so as to finally form pre-plasticized polyvinyl alcohol granules with fluffy particles, good toughness and clean appearance; the compound plasticizer is composed of water and glycerin, and the volume ratio of water to glycerin is 1:5; the stirring temperature is 120°C, and the stirring speed is 80rpm.

[0045] The preparation method of thermoplastic starch is as follows: 90 parts of corn starch are mixed with 15 parts of glycerol, 15 parts of acetyl tributyl citrate, 1 part of stearic acid, 7 parts of acetyl tributyl citrate and 1.5 parts of coupling agent, and stirred in a high-speed mixer for 12 minutes, and sealed and left to stand for 14 hours; then the mixture is transported to a twin-screw extruder for granulation to obtain thermoplastic starch granules; the temperature of each heating section of the extruder is 140-150°C, the screw speed is 60rpm, and the feeding speed is set to 3rpm. The coupling agent is an aluminate coupling agent.

[0046] The modified cellulose is cellulose modified with stearic acid; the preparation method of the cellulose modified with stearic acid is as follows:

[0047] Mix 1 part of cellulose with 25 parts of anhydrous ethanol, and perform ultrasonic treatment for 35 minutes. Then add 3 parts of stearic acid and continue the ultrasonic treatment for 25 minutes. Then, heat and stir the mixture at 85°C for 3 hours, filter, and dry.

[0048] Example 3

[0049] The preparation method of pre-plasticized polyvinyl alcohol is as follows: 60 parts of a compound plasticizer are divided into three parts, and the parts are added into 120 parts of polyvinyl alcohol being stirred in three batches, with an interval of 10 minutes between each batch, and the last batch of compound plasticizer is added and stirred for 20 minutes, so as to finally form pre-plasticized polyvinyl alcohol granules with fluffy particles, good toughness and clean appearance; the compound plasticizer is composed of water and glycerin, and the volume ratio of water to glycerin is 1:5; the stirring temperature is 80°C, and the stirring speed is 120rpm.

[0050] The preparation method of thermoplastic starch is as follows: 110 parts of corn starch are mixed with 25 parts of glycerol, 25 parts of acetyl tributyl citrate, 3 parts of stearic acid, 9 parts of acetyl tributyl citrate and 0.5 parts of coupling agent, and stirred in a high-speed mixer for 8 minutes, and sealed and left to stand for 10 hours; then the mixture is transported to a twin-screw extruder for granulation to obtain thermoplastic starch granules; the temperature of each heating section of the extruder is 145-155°C, the screw speed is 40rpm, and the feeding speed is set to 5rpm. The coupling agent is a silane coupling agent.

[0051] The modified cellulose is cellulose modified with stearic acid; the preparation method of the cellulose modified with stearic acid is as follows: 3 parts of cellulose are mixed with 15 parts of anhydrous ethanol, ultrasonically treated for 25 minutes, then 1 part of stearic acid is added, and ultrasonic treatment is continued for 35 minutes, and then heated and stirred at 75°C for 5 hours, filtered, and dried.

[0052] In the following examples and comparative examples, pre-plasticized polyvinyl alcohol, thermoplastic starch, and stearic acid-modified cellulose are products prepared by the method of Example 1.

[0053] Comparative Example 1

[0054] The invention discloses a high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film, which is prepared from the following raw materials in parts by weight: 50 parts of pre-plasticized polyvinyl alcohol, 50 parts of thermoplastic starch, 0 parts of cellulose surface-modified with stearic acid (M-CSC), 0 parts of citric acid, 0.3 parts of tea polyphenols, 0.2 parts of antioxidant 1010, and 1 part of stearic acid.

[0055] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, the pre-mixing speed is 300rpm at room temperature, and the pre-mixing time is 5min; then, the materials enter the extruder section for plasticization and are extruded through the die, the temperature of each section of the extrusion section is controlled to be 160-170℃, the die temperature is 210℃, the single screw speed is set to 60rpm, and the thickness of the extruder extruded sheet is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling of compressed air at the extruder die, and the compressed air pressure of the film blowing section is 0.6MPa; the film stretching rate is set to 350mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and obtaining the final degradable polyvinyl alcohol-thermoplastic starch food preservative film. The thickness of the food preservative film is 25μm.

[0056] Comparative Example 2

[0057] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 55 parts of polyvinyl alcohol, 45 parts of thermoplastic starch, 0 parts of cellulose surface modified by stearic acid (M-CSC), 0 parts of citric acid, 0.3 parts of tea polyphenols, 0.2 parts of antioxidant 1010, and 1 part of stearic acid.

[0058] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, the pre-mixing speed is 300rpm at room temperature, and the pre-mixing time is 5min; then, the materials enter the extruder section for plasticization and are extruded through the die, the temperature of each section of the extrusion section is controlled to be 160-170℃, the die temperature is 210℃, the single screw speed is set to 60rpm, and the thickness of the extruder extruded sheet is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling of compressed air at the die of the extruder, and the compressed air pressure of the film blowing section is 0.6MPa; the film stretching rate is set to 350mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and then the final degradable polyvinyl alcohol-thermoplastic starch food preservative film is obtained. The thickness of the food preservative film is 30μm.

[0059] Comparative Example 3

[0060] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 60 parts of pre-plasticized polyvinyl alcohol, 40 parts of thermoplastic starch, 0 parts of cellulose surface modified by stearic acid (M-CSC), 0 parts of citric acid, 0.3 parts of tea polyphenols, 0.2 parts of antioxidant 1010, and 1 part of stearic acid.

[0061] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, the pre-mixing speed is 300rpm at room temperature, and the pre-mixing time is 5min; then, the materials enter the extruder section for plasticization and are extruded through the die, the temperature of each section of the extrusion section is controlled to be 160-170℃, the die temperature is 210℃, the single screw speed is set to 60rpm, and the thickness of the extruder extruded sheet is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling of compressed air at the die of the extruder, and the compressed air pressure of the film blowing section is 0.6MPa; the film stretching rate is set to 350mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and then the final degradable polyvinyl alcohol-thermoplastic starch food preservative film is obtained. The thickness of the food preservative film is 28μm.

[0062] Comparative Example 4

[0063] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 65 parts of pre-plasticized polyvinyl alcohol, 35 parts of thermoplastic starch, 0 parts of cellulose surface modified by stearic acid (M-CSC), 0 parts of citric acid, 0.3 parts of tea polyphenols, 0.2 parts of antioxidant 1010, and 1 part of stearic acid.

[0064] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, the pre-mixing speed is 300rpm at room temperature, and the pre-mixing time is 5min; then, the materials enter the extruder section for plasticization and are extruded through the die, the temperature of each section of the extrusion section is controlled to be 160-170℃, the die temperature is 210℃, the single screw speed is set to 60rpm, and the thickness of the extruder extruded sheet is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling of compressed air at the extruder die, and the compressed air pressure in the film blowing section is 0.6MPa; the film stretching rate is set to 350mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and obtaining the final degradable polyvinyl alcohol-thermoplastic starch food preservative film. The thickness of the food preservative film is 35μm.

[0065] Table 1. Properties of polyvinyl alcohol-thermoplastic starch films prepared in Comparative Examples 1-4

[0066] project Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Tensile strength / MPa 12.3 16.5 18.7 21.2 Elongation at break / % 235.6 202.5 332.1 312.0 Tear strength / KN / m 25.1 32.4 39.8 43.2 Appearance Slightly yellow, slightly rough Light yellow, smooth Light yellow, smooth White, smooth transparency / % 78 75 70 60

[0067] The processing technology and other formula ratios were fixed, and only the ratio of polyvinyl alcohol to thermoplastic starch in the formula was changed. From the data in Table 1, it can be found that with the reduction of the ratio of thermoplastic starch, the appearance of the composite system gradually improved, the burnt smell and smoke phenomenon decreased, the color changed from slightly yellow transparent to white translucent, and the transparency decreased, indicating that there was a certain incompatibility between the two; with the increase of the proportion of polyvinyl alcohol, the tensile strength and tear strength of the material gradually increased, while the fracture productivity showed a trend of first decreasing and then increasing. Considering the appearance and performance comprehensively, the ratio of polyvinyl alcohol to thermoplastic starch was determined to be 65:35.

[0068] Comparative Example 5

[0069] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 65 parts of pre-plasticized polyvinyl alcohol, 35 parts of thermoplastic starch, 0 parts of cellulose surface modified with stearic acid (M-CSC), 1 part of citric acid, 0.3 parts of tea polyphenols, 0.2 parts of antioxidant 1010, and 1 part of stearic acid.

[0070] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), cross-linking agent, antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, the pre-mixing speed is 300rpm at room temperature, and the pre-mixing time is 5min; then, the materials enter the extruder section for plasticization, slight cross-linking and extrusion through the die, the temperature of each section of the extrusion section is controlled to be 160-170℃, the die temperature is 210℃, the single screw speed is set to 60rpm, and the thickness of the extruder extruded sheet is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling of compressed air at the extruder die, and the compressed air pressure in the film blowing section is 0.6MPa; the film stretching rate is set to 350mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and obtaining the final degradable polyvinyl alcohol-thermoplastic starch food preservative film. The thickness of the food preservative film is 32μm.

[0071] Comparative Example 6

[0072] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 65 parts of pre-plasticized polyvinyl alcohol, 35 parts of thermoplastic starch, 0 parts of cellulose surface modified by stearic acid (M-CSC), 3 parts of citric acid, 0.3 parts of tea polyphenols, 0.2 parts of antioxidant 1010, and 1 part of stearic acid.

[0073] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), cross-linking agent, antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, the pre-mixing speed is 300rpm at room temperature, and the pre-mixing time is 5min; then, the materials enter the extruder section for plasticization, slight cross-linking and extrusion through the die, the temperature of each section of the extrusion section is controlled to be 160-170℃, the die temperature is 210℃, the single screw speed is set to 60rpm, and the thickness of the extruder extruded sheet is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling of compressed air at the extruder die, and the compressed air pressure in the film blowing section is 0.6MPa; the film stretching rate is set to 350mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and obtaining the final degradable polyvinyl alcohol-thermoplastic starch food preservative film. The thickness of the food preservative film is 33μm.

[0074] Comparative Example 7

[0075] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 65 parts of pre-plasticized polyvinyl alcohol, 35 parts of thermoplastic starch, 0 parts of cellulose surface modified with stearic acid (M-CSC), 1 part of citric acid, 0.3 parts of tea polyphenols, 0.2 parts of antioxidant 1010, and 1 part of stearic acid.

[0076] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), cross-linking agent, antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, the pre-mixing speed is 300rpm at room temperature, and the pre-mixing time is 5min; then, the materials enter the extruder section for plasticization, slight cross-linking and extrusion through the die, the temperature of each section of the extrusion section is controlled to be 160-170℃, the die temperature is 210℃, the single screw speed is set to 60rpm, and the thickness of the extruder extruded sheet is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling of compressed air at the extruder die, and the compressed air pressure of the film blowing section is 0.6MPa; the film stretching rate is set to 350mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and finally the final degradable polyvinyl alcohol-thermoplastic starch food preservative film is obtained. The thickness of the food preservative film is 29μm.

[0077] Table 2. Properties of polyvinyl alcohol-thermoplastic starch films prepared in Comparative Examples 4-7

[0078]

[0079]

[0080] The ratio of polyvinyl alcohol and thermoplastic starch in the system and other conditions were fixed, and only the amount of cross-linking agent citric acid was changed. The relevant properties are shown in Table 2. From Table 2, it can be analyzed that with the increase in the amount of cross-linking agent, the tensile strength and tear strength of the material first increased and then decreased, and the appearance changed from white translucent to white transparent, and finally the color became darker. The reason may be that slight cross-linking helps the combination of the two-phase interface and helps the homogeneous distribution of PVA and thermoplastic starch, resulting in increased transparency, but excessive cross-linking makes the starch molecular weight longer, making processing difficult, resulting in aggravated decomposition, and thus performance degradation.

[0081] Example 4

[0082] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 65 parts of pre-plasticized polyvinyl alcohol, 35 parts of thermoplastic starch, 2.5 parts of cellulose surface-modified with stearic acid (M-CSC), 1 part of citric acid, 0.3 parts of tea polyphenols, 0.2 parts of antioxidant 1010, and 1 part of stearic acid.

[0083] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), stearic acid-modified cellulose, cross-linking agent, antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, and the premixing speed is 300rpm at room temperature, and the premixing time is 5min; then, the materials enter the extruder section for plasticization, slight cross-linking and extrusion through the die, the temperature of each section of the extrusion section is controlled to be 160-170°C, the die temperature is 220°C, the single screw speed is set to 60rpm, and the thickness of the extruded sheet of the extruder is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling effect of compressed air at the extruder die, and the compressed air pressure in the film blowing section is 0.6MPa; the film stretching rate is set to 350mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and obtaining the final degradable polyvinyl alcohol-thermoplastic starch food preservative film. The thickness of food cling film is 34μm.

[0084] Example 5

[0085] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 65 parts of pre-plasticized polyvinyl alcohol, 35 parts of thermoplastic starch, 5 parts of cellulose surface-modified with stearic acid (M-CSC), 1 part of citric acid, 0.3 parts of tea polyphenols, 0.2 parts of antioxidant 1010, and 1 part of stearic acid.

[0086] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), stearic acid-modified cellulose, cross-linking agent, antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, and the premixing speed is 300rpm at room temperature, and the premixing time is 5min; then, the materials enter the extruder section for plasticization, slight cross-linking and extrusion through the die, the temperature of each section of the extrusion section is controlled to be 160-170°C, the die temperature is 220°C, the single screw speed is set to 60rpm, and the thickness of the extruded sheet of the extruder is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling effect of compressed air at the extruder die, and the compressed air pressure in the film blowing section is 0.6MPa; the film stretching rate is set to 350mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and obtaining the final degradable polyvinyl alcohol-thermoplastic starch food preservative film. The thickness of food cling film is 31μm.

[0087] Table 3. Related properties of polyvinyl alcohol-thermoplastic starch films prepared in Comparative Example 6 and Examples 4-5

[0088]

[0089] The ratio of polyvinyl alcohol and thermoplastic starch, the amount of crosslinking agent and other conditions in the system are fixed, and only the amount of stearic acid modified cellulose is changed. The relevant properties are shown in Table 3. From the analysis of Table 3, it can be seen that with the increase of the amount of modified cellulose, the tensile strength and tear strength first increase and then decrease, which may be due to the uneven dispersion and deterioration of processing performance caused by excessive cellulose dosage; the elongation at break and transparency gradually decrease; the water vapor permeability coefficient and oxygen permeability show a trend of first decreasing and then increasing, because the layered or network structure formed by cellulose in the system can block the diffusion of oxygen and water vapor. If the dosage is too large, cellulose will agglomerate and the barrier performance will deteriorate.

[0090] Example 6

[0091] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 50 parts of pre-plasticized polyvinyl alcohol, 40 parts of thermoplastic starch, 1 part of cellulose surface-modified with stearic acid (M-CSC), 0.1 parts of citric acid, 0.5 parts of tartaric acid, 1 part of vitamin E, and 3 parts of silicone.

[0092] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), stearic acid-modified cellulose, cross-linking agent, antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, and the premixing speed is 400rpm at room temperature, and the premixing time is 3min; then, the materials enter the extruder section for plasticization, slight cross-linking and extrusion through the die, the temperature of each section of the extrusion section is controlled to be 170-180°C, the die temperature is 210°C, the single screw speed is set to 100rpm, and the thickness of the extruded sheet of the extruder is 500μm; the plasticized sheet is shaped by the expansion, stretching and cooling of compressed air at the die of the extruder, and the compressed air pressure in the film blowing section is 0.7MPa; the film stretching rate is set to 200mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and obtaining the final degradable polyvinyl alcohol-thermoplastic starch food preservative film. The thickness of food cling film is 33μm.

[0093] Example 7

[0094] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 60 parts of pre-plasticized polyvinyl alcohol, 50 parts of thermoplastic starch, 10 parts of cellulose surface-modified with stearic acid (M-CSC), 3 parts of citric acid, 0.1 parts of benzoic acid, 0.1 parts of phenolic antioxidant, and 2 parts of polyethylene wax powder.

[0095] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), stearic acid-modified cellulose, cross-linking agent, antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, and the premixing speed is 500rpm at room temperature, and the premixing time is 4min; then, the materials enter the extruder section for plasticization, slight cross-linking and extrusion through the die, the temperature of each section of the extrusion section is controlled to be 165-175°C, the die temperature is 205°C, the single screw speed is set to 80rpm, and the thickness of the extruded sheet of the extruder is 700μm; the plasticized sheet is shaped by the expansion, stretching and cooling effect of compressed air at the extruder die, and the compressed air pressure in the film blowing section is 0.8MPa; the film stretching rate is set to 450mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and obtaining the final degradable polyvinyl alcohol-thermoplastic starch food preservative film. The thickness of food cling film is 28μm.

[0096] Example 8

[0097] The preparation of high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film is prepared from the following raw materials in parts by weight: 55 parts of pre-plasticized polyvinyl alcohol, 45 parts of thermoplastic starch, 8 parts of cellulose surface-modified with stearic acid (M-CSC), 2 parts of citric acid, 0.4 parts of tartaric acid, 0.5 parts of vitamin E, and 1.5 parts of silicone.

[0098] The above materials are prepared by the following processing flow: pre-plasticized polyvinyl alcohol (PVA), thermoplastic starch (TPS), stearic acid-modified cellulose, cross-linking agent, antibacterial agent, antioxidant, lubricant, etc. are transported from the storage bin to the mixing hopper through the feeding system according to the ratio, and the pre-mixing speed is 450rpm at room temperature, and the pre-mixing time is 5min; then, the materials enter the extruder section for plasticization, slight cross-linking and extrusion through the die, the temperature of each section of the extrusion section is controlled to be 160-170°C, the die temperature is 215°C, the single screw speed is set to 70rpm, and the thickness of the extruded sheet of the extruder is 800μm; the plasticized sheet is shaped by the expansion, stretching and cooling effect of compressed air at the extruder die, and the compressed air pressure in the film blowing section is 0.6MPa; the film stretching rate is set to 300mm / min; finally, the polyvinyl alcohol-thermoplastic starch composite film is packaged after traction, testing, winding, slitting, and obtaining the final degradable polyvinyl alcohol-thermoplastic starch food preservative film. The thickness of food cling film is 34μm.

[0099] Table 4. Related properties of polyvinyl alcohol-thermoplastic starch films prepared in Examples 6-8

[0100]

[0101] In summary, the polyvinyl alcohol-thermoplastic starch food packaging film prepared in the embodiment of the present invention is prepared through reasonable material system design and structure regulation. The polyvinyl alcohol-thermoplastic starch film is not only biodegradable, but the composite film also has excellent mechanical properties, processing properties and water vapor barrier properties, the material cost is controllable, and it has great industrialization prospects.

[0102] The above examples are implementation methods of part of the present invention, but the implementation methods of the present invention are not limited to the above implementation cases. Any other changes, substitutions, modifications, combinations, and simplifications that do not deviate from the spirit and design principles of the present invention should be regarded as equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film, characterized in that: The invention is prepared from the following raw materials in parts by weight: 50-65 parts of pre-plasticized polyvinyl alcohol, 35-50 parts of thermoplastic starch, 1-10 parts of modified cellulose, 0.1-3 parts of a cross-linking agent, 0.1-0.5 parts of an antibacterial agent, 0.1-1 parts of an antioxidant and 1-3 parts of a lubricant.

2. The high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 60-65 parts of pre-plasticized polyvinyl alcohol, 40-50 parts of thermoplastic starch, 1-5 parts of modified cellulose, 0.1-3 parts of cross-linking agent, 0.1-0.5 parts of antibacterial agent, 0.1-1 parts of antioxidant and 1-3 parts of lubricant.

3. The high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film according to claim 1, characterized in that: The pre-plasticized polyvinyl alcohol is prepared by the following method: Divide the compound plasticizer into three parts and add them into the stirred polyvinyl alcohol in three batches, with an interval of 10-20 minutes between each batch. After adding the last batch of compound plasticizer, stir for 10-20 minutes. The compound plasticizer is composed of water and glycerol, and the volume ratio of water to glycerol is 1:5; The ratio of the polyvinyl alcohol to the compound plasticizer is (4-6):3; The stirring temperature is 80-120° C., and the stirring speed is 80-120 rpm.

4. The high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film according to claim 1, characterized in that: The thermoplastic starch is prepared by the following method: Mix 90-110 parts of corn starch with 15-25 parts of glycerol, 15-25 parts of acetyl tributyl citrate, 1-3 parts of stearic acid, 7-9 parts of acetyl tributyl citrate and 0.5-1.5 parts of coupling agent, stir in a mixer for 8-12 minutes, seal and let stand for 10-14 hours; then use an extruder to granulate; The temperature of each heating section of the extruder is 140-155° C., the screw speed is 40-60 rpm, and the feeding speed is set to 3-5 rpm.

5. The high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film according to claim 1, characterized in that: The modified cellulose is stearic acid-modified cellulose; The stearic acid-modified cellulose is prepared by the following method: Mix 1-3 parts of cellulose with 15-25 parts of anhydrous ethanol, and perform ultrasonic treatment for 25-35 minutes. Then, add 1-3 parts of stearic acid, and continue the ultrasonic treatment for 25-35 minutes. Then, heat and stir the mixture at 75-85°C for 3-5 hours, filter, and dry.

6. The high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film according to claim 1, characterized in that: The cross-linking agent is citric acid; The antibacterial agent is one of citric acid, tartaric acid, plant essential oil, tea polyphenols, apple pomace polyphenols, grapefruit seed extract, benzoic acid, and lauroyl arginine ethyl ester hydrochloride.

7. The high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film according to claim 1, characterized in that: The antioxidant is at least one of phenolic antioxidants, vitamin E, thioesters, and phosphite antioxidants.

8. The high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film according to claim 1, characterized in that: The lubricant is one of stearic acid, acrylate, polyethylene wax powder and silicone.

9. The high-performance degradable polyvinyl alcohol-thermoplastic starch food preservative film according to claim 4, characterized in that: The coupling agent is one of a silane coupling agent, a titanate coupling agent and an aluminate coupling agent.

10. A method for preparing a high-performance biodegradable polyvinyl alcohol-thermoplastic starch food preservative film as described in claims 1-9, characterized in that: The following steps are involved: S1. Mix the raw materials according to the proportion, mix them evenly, remove impurities, and then enter the extrusion section; the premixing speed is 300-500 rpm, the premixing time is 3-5 min, and the temperature is room temperature; S2, using a single screw extruder to extrude through a die to obtain a polymer annular sheet; the extrusion section temperature is 160-180°C, the die temperature is 205-220°C, the single screw speed is set to 60-100rpm, and the extruder extruded sheet thickness is 500-800μm; S3, blowing the sheet through compressed air at the die of the extruder to form and stretch it to obtain a semi-finished fresh-keeping film; the compressed air pressure for blowing the film is 0.6-0.8 MPa; the film stretching rate is set to 200-450 mm / min; S4, rolling up the semi-finished cling film and then cutting it into pieces to obtain a food cling film, wherein the thickness of the food cling film is 25-35 μm.

Citation Information

Patent Citations

  • Modified polyvinyl alcohol food fresh-keeping film and preparation method thereof

    CN118126479A

  • Preparation method of walnut shell lignin enhanced polyvinyl alcohol food preservative film

    CN118580533A

Cited By

  • A plastic product for sealing and preserving freshness and a method for manufacturing the same

    CN122647865A